The Language of Power: A Sociolinguistic Study of Social Status in little women by Greta Gerwig: English - Arifin, Resti Permata Arifin (CV. Kalimasada Group Profesional, 2023)
The purpose of this sociolinguistic research is to provide an in-depth analysis of language use as a reflection of power dynamics and social status in Greta Gerwig little Women (2019). This research uses a combination of film analysis and sociolinguistic theory to examine how language is used to communicate and influence power dynamics and social differences among the characters. Data was collected by closely observing the film, focusing on the language choices and communication strategies used by the characters. The analysis explores the complex nuances of language use in the context of social relations, examining differences in language use among different social groups, and the role of gender in shaping language patterns. The results highlight the interplay between language, power and social status in the story of the film